Gene therapies for transfusion dependent β‐thalassemia: Current status and critical criteria for success. Issue 9 (20th August 2020) - Soni, Sandeep
Abstract: Thalassemia is one of the most prevalent monogenic diseases usually caused by quantitative defects in the production of β‐globin leading to severe anemia. Technological advances in genome sequencing, stem cell selection, viral vector development, transduction and gene editing strategies now allow for efficient ex‐vivo genetic manipulation of human stem cells that can lead to production of hemoglobin, leading to a meaningful clinical benefit in thalassemia patients. In this review, the status of the gene‐therapy approaches available for transfusion dependent thalassemia are discussed, along with the critical criteria that affect efficacy and lessons that have been learned from the early phase clinical trials. Salient steps necessary for the clinical development, manufacturing, and regulatory approvals of gene therapies for thalassemia are also highlighted, so that the potential of these therapies can be realized. It is highly anticipated that gene therapies will soon become a treatment option for patients lacking compatible donors for hematopoietic stem cell transplant and will offer an alternative for definitive treatment of β‐thalassemia.